Neuromodulation in eating disorders and obesity: a promising way of treatment? - Jáuregui-Lobera I (Dove Medical Press, 2018)
Ignacio Jáuregui-Lobera,1 José V Martínez-Quiñones2 1Department of Molecular Biology and Biochemical Engineering, University of Pablo de Olavide of Seville, Seville, Spain; 2Department of Neurosurgery, Mutua de Accidentes de Zaragoza (Servicio de Neurocirugía), Zaragoza, Spain Abstract: Neuromodulation can affect the functioning of the central nervous system (CNS), and emotional/eating behavior is an exciting facet of that functioning. Therefore, it would be possible to offer an alternative (or complement) treatment to psychotropic medications and different psychological and nutritional approaches to both eating disorders (EDs) and obesity. Although there are a number of publications in these areas, a systematic review has not been conducted to date. Abstracts, letters, conference reports, dissertations, and reviews were excluded. Clinical trials and controlled human clinical trials were filtered and included in this study. Articles included were based on the population suffering from anorexia nervosa, bulimia nervosa, binge ED, overweight, and obesity. No restrictions were placed on the sample size. Only trials investigating the effect of neuromodulation by means of deep brain stimulation (DBS), transcranial direct current stimulation (tDCS), and transcranial magnetic stimulation (TMS) were included. The following databases were used to conduct the search: MEDLINE/PubMed, PsycINFO, PsycArticles, and Cochrane (Search Trials, CENTRAL). Study selection was performed following the PRISMA process (PRISMA 2009 Checklist). The total number of participants in all the trials was 562 (DBS, 25; tDCS, 138; TMS, 399; range, 3–90; median, 23.5). As a result, 50% of the studies had samples of between 14 and 38 participants. Neuromodulation in ED seems to have certain clinical potential, and therefore, this is a promising area for further research. Developments in ED neuromodulation will be linked to neuroimaging to identify potential stimulation targets and possible biomarkers of treatment response. To date, TMS and/or direct current stimulation (DCS) is not the first-line treatment yet, but it could become a preferred option of treatment in the future. Further studies should avoid small sample sizes and the use of different methodologies. Currently, neuromodulation techniques are in the experimental phase, and they are not an evidence-based treatment for ED. Keywords: deep brain stimulation, transcranial direct current stimulation, transcranial magnetic stimulation, anorexia nervosa, bulimia nervosa, obesity